Nilai Religiusitas dalam Novel Layla Karya Candra Malik - Ubaidillah, Rizal; Suprapto, Suprapto (STKIP PGRI Ponorogo Press, 2024)
Abstract: Literature generally talks about human and social problems. With a distinctive presentation, literature is rich contained with values, one of them is religious value. Novel Layla by Candra Malik is a novel that has a number of religious values that are interesting to study. The goals of this research were to influence the attitudes and actions of human being, provide awareness to do good deeds and understanding of religious values as a builder of faith. The method used was descriptive qualitative study. The teaching within the religious literature includes unlimited problems; related of life and living, which includes the whole issue of human dignity. Broadly speaking, the issues of life and living include: (a) the human relationship with God, (b) the human relationship with another human being, (c) problem of man's relationship with himself. Keywords: Sociology of literature, religious values, the novel Layla.